Essays in Archaeology and Archaeometry and the Hellenic Contribution to Egyptology - Nikolaos Lazaridis; Omar Abdel-Kareem; Grigorios Tsokas (Heritage, 2022)
The contemporary trend of research projects and works are presented on selective issues of archaeometry, archaeology and Egyptology. The current status in research in the area of SE Mediterranean on cultural heritage and archaeological/historical reflections alone and/or coupled with archaeological sciences of eleven papers are placed within an updated frame. The results concern a variety of selected topics critically presented. The topics touch on the cultural astronomy, the ancient textiles and masonries and the physico-chemical and biological investigations, the socio-political issues of Egyptian Ramesside era, revisiting the inscription of an Egyptian statuette, and the valuable information extracted from rock graffiti in north Kharga, Egypt.